PENGARUH PENGGUNAAN BIRTH BALL TERHADAP PENURUNAN NYERI PERSALINAN KALA I FASE AKTIF PADA PRIMIGRAVIDA - Dasiana Marawita; Desi Soraya; Danny Putri (JURNAL FISIOTERAPI DAN ILMU KESEHATAN SISTHANA, 2023)
Management of labor pain is an attempt to reduce MMR. Labor pain must be treated in an effective way because if the pain is accompanied by a stress reaction, it will have harmful side effects for the mother and also the fetus. The midwife at the Ngesrep Health Center has never used birth balls as an intervention to treat inpartu mothers. The purpose of this study was to determine the effect of using a birth ball on reducing labor pain in the active phase of the 1st stage. This type of research is a quasi-experimental design with one group pretest posttest design. The population in this study were all mothers with an estimated day of birth in July to August 2022 who will give birth at the Ngesrep Health Center Semarang. The sampling technique was purposive sampling and the number of samples was 31 people. Data collection tools used in this study include Standard Operating Procedures (SOP), Birth Ball Techniques, Numerical Rating Scale (NRS), Observation Sheets and birth balls with a diameter of 55 cm or 65 cm. Data analysis was carried out using the paired sample t test. The results of the study obtained a t value of 9.613 which means that every 1 time birth ball intervention with 4 movements for 30 minutes makes the primigravida have the potential to be 9.613 times to be able to reduce labor pain in the active phase of the 1st stage. The p-value is 0.000 <0.05, so the hypothesis (H0) is rejected and (Ha) is accepted, so it can be concluded that there is an effect of using birth balls on reducing labor pain in the active phase of the 1st stage of labor in primigravida at Ngesrep Health Center Semarang. For health services, it is expected that the use of birth balls can be used as an alternative to reduce labor pain in the active phase of the 1st stage of primigravida.